2022
DOI: 10.1002/cpp.2776
|View full text |Cite
|
Sign up to set email alerts
|

Overprotective parenting experiences and early maladaptive schemas in adolescence and adulthood: A systematic review and meta‐analysis

Abstract: Young's schema model identifies overprotection as a type of childhood experience associated with early maladaptive schemas. This review evaluated the evidence base examining overprotective parenting as a predictor of schema endorsement in adolescence and adulthood. A systematic review and meta‐analysis were conducted in accordance with the PRISMA guidelines, and registered on PROSPERO (CRD42021258990). PsycINFO, CINAHL and PubMed databases were searched on 5 June 2021 for eligible studies reporting original da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Impaired autonomy was also associated—but only indirectly—with all subscales of aggression. The characteristics of this domain, including vulnerability, sense of personal failure, excessive dependence on others, and poor social functioning (Bruysters & Pilkington, 2022), are thought to encourage poor self‐esteem, over‐dependence on and enmeshment with others, and the use of aggression and other forms of manipulation to maintain continued dependence on others (Shorey et al, 2015). This EMS domain has been found to be associated with aggression toward intimate partners (Gay et al, 2013; Kachadourian et al, 2013), and in the present study was found to be directly associated with both indirect aggression and hostility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired autonomy was also associated—but only indirectly—with all subscales of aggression. The characteristics of this domain, including vulnerability, sense of personal failure, excessive dependence on others, and poor social functioning (Bruysters & Pilkington, 2022), are thought to encourage poor self‐esteem, over‐dependence on and enmeshment with others, and the use of aggression and other forms of manipulation to maintain continued dependence on others (Shorey et al, 2015). This EMS domain has been found to be associated with aggression toward intimate partners (Gay et al, 2013; Kachadourian et al, 2013), and in the present study was found to be directly associated with both indirect aggression and hostility.…”
Section: Discussionmentioning
confidence: 99%
“…The impaired limits domain describes a sense of entitlement, diminished self‐control, sense of superiority, and difficulty respecting the rights of others (Chodkiewicz et al, 2022). The impaired autonomy domain describes vulnerability, sense of personal failure, excessive dependence on others, and poor social functioning (Bruysters & Pilkington, 2022). The over‐vigilance/inhibition domain describes excessive need for the approval of others, subjugation of one's own needs and emotions, punitiveness, and tendency toward emotional inhibition, negativity, and pessimism (Young et al, 2003).…”
Section: Introductionmentioning
confidence: 99%